Gambaran Kunjungan Pasien di Ruang Bertekanan Negatif Semasa Pandemi Covid-19 - J. Widijanto Sudhana; Priscilla Aurelia (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Dental and oral health is important to maintain a healthy body, the prevalence of dental and oral problems in DKI Jakarta was as high as 59.1% and only 16.4% received services. After the outbreak of Covid-19 pandemic, people felt anxious visiting dentist for fear of being infected. This caused a change in the pattern of patient visit. Objectives: To describe patient visit at RSGM-P USAKTI before and after the operation of negative pressure room. Methods: Descriptive observational study with a cross-sectional design to describe patient visit at RSGM-P USAKTI before and after the operation of negative pressure room in 2019-2021. Results: A total of 21,761 visits were recorded before the pandemic. There was a decrease before (1,472 visits) and an increase (5,929 visits) after the operation of negative pressure room. Female patients were more recorded. During pandemic there was a decrease especially in patients aged ≤11.9 years, number of caries cases increased, and visits after the negative pressure room was operational during the pandemic increased. Conclusion: Patients visit decreased before and increased after the negative pressure room operated. However, counseling regarding the importance of negative pressure rooms to public is crucial.